Factors affecting irreversible inhibition of EGFR and influence of chirality on covalent binding - Pasquale A. Morese; Ayaz Ahmad; Mathew P. Martin; Richard A. Noble; Sara Pintar; Lan Z. Wang; Shangze Xu; Andrew Lister; Richard A. Ward; Agnieszka K. Bronowska; Martin E. M. Noble; Hannah L. Stewart; et al. (Communications Chemistry)
Abstract The discovery of targeted covalent inhibitors is of increasing importance in drug discovery. Finding efficient covalent binders requires modulation of warhead reactivity and optimisation of warhead geometry and non-covalent interactions. Uncoupling the contributions that these factors make to potency is difficult and best practice for a testing cascade that is pragmatic and informative is yet to be fully established. We studied the structure-reactivity-activity relationships of a series of analogues of the EGFR inhibitor poziotinib with point changes in two substructural regions as well as variations in warhead reactivity and geometry. This showed that a simple probe displacement assay that is appropriately tuned in respect of timing and reagent concentrations can reveal structural effects on all three factors: non-covalent affinity, warhead reactivity and geometry. These effects include the detection of potency differences between an enantiomeric pair that differ greatly in their activity and their capacity to form a covalent bond. This difference is rationalised by X-ray crystallography and computational studies and the effect translates quantitatively into cellular mechanistic and phenotypic effects.